Sistema de medição e controle do consumo de água utilizando Rede de Sensores Sem Fio - da Silva, Marcos; Pereira, Daniel (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2011: Anais do I Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2011)
Water has becoming a commodity of rising costs and increasingly scare. Currently, the waste is being pointed out as a major enemy to be combated, as the population in general does not give due weight to the liquid of life, whichever is the illusion of an inexhaustible well, many places do not have water potable. This paper presents the prototype of a system of measurement and control of water through Wireless Sensor Network. The system aims to educate the user presenting the daily graph for separate rooms in home or industries. In addition, the system can help detect leaks.